The Role of Positive Emotion in Mediating the Effect of Price Perception on Impulse Buying : A Study on Circle K Customers in Denpasar City (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The rapid growth of modern retail competition requires companies to understand key drivers of consumer purchasing behavior, particularly impulse buying. This study examines the influence of price perception on impulse buying, with positive emotion as the mediating variable. Data were collected from 100 Circle K customers in Denpasar City using a purposive sampling method. Responses were collected through questionnaires and analyzed using Path Analysis and Sobel Test. The findings show that price perception has a positive and significant effect on impulse buying and positive emotion, and positive emotion has a positive and significant effect on impulse buying. Further, positive emotion is a significant mediator in the relationship between price perception and impulse buying. These findings support Cognitive Appraisal Theory, suggesting that favorable price perceptions of sales promotions can evoke positive emotional responses, which in turn encourage impulse buying behavior among Circle K customers in Denpasar City.